Water Research - Water Research (Elsevier, 2026)
Water Research is an interdisciplinary journal with an applied edge. This means that papers that go into too many details of one of the supporting disciplines (such as chemistry, toxicology, microbiology, material sciences, etc.) without making a good link with water research in general may be rejected up-front. More information on types of manuscripts that are not suitable for Water Research are discussed in an editorial available here. Audience: Biologists, chemical engineers, chemists, civil engineers, environmental engineers, limnologists, and microbiologists.
FI 2.13
Q1
Keywords: Earth; Space & Environmental Sciences; Water Resource Management; Acuerdos transformativos; Transformative agreements; Calidad del agua; Tratamiento de agua; Aguas residuales; Contaminación hídrica; Ciclo del agua; Gestión del agua